2010
DOI: 10.1590/s1413-86702010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of hemolysis in patients with P. vivax malaria treated with primaquine, in the Brazilian Amazon

Abstract: This report describes the development of hemolysis in eighteen glucose-6-phosphate dehydrogenase defi cient patients treated for Plasmodium vivax malaria with chloroquine and primaquine. The most frequent fi ndings accompanying hemolysis were fever and leukocytosis, in addition to anemia requiring red blood cell transfusion, and development of acute renal failure. Hemolysis in patients using primaquine is not infrequent and contributes to the morbidity of infection caused by Plasmodium vivax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In Panama, a mutation analysis revealed that a Mediterranean variant was behind the development of kernicterus after exposure to naphthalene in a male patient (de Gurrola et al 2008). In Manaus, Brazil, G6PDd was associated with a considerably higher risk of malaria-related transfusions, suggesting that G6PDd may contribute to a considerable proportion of malaria-related complications in an area with an unexpectedly high prevalence of the Mediterranean variant (Ramos-Júnior et al 2010, Lacerda et al 2012a, Santana et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…In Panama, a mutation analysis revealed that a Mediterranean variant was behind the development of kernicterus after exposure to naphthalene in a male patient (de Gurrola et al 2008). In Manaus, Brazil, G6PDd was associated with a considerably higher risk of malaria-related transfusions, suggesting that G6PDd may contribute to a considerable proportion of malaria-related complications in an area with an unexpectedly high prevalence of the Mediterranean variant (Ramos-Júnior et al 2010, Lacerda et al 2012a, Santana et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…It is the only drug proven to be effective, and licensed to eliminate, the hypnozoites of Plasmodium vivax and Plasmodium ovale . Though primaquine is effective, unique and irreplaceable, it is also associated with serious hazards and side effects, such as its ability to precipitate haemolysis in glucose-6-phosphate dehydrogenase (G6PD) deficient individuals [3]. This prohibits its use in key groups, such as pregnant women [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although there was strong evidence of the deficient status being protective to malaria infection, individuals with reduced G6PD activity reported a higher incidence of jaundice and blood transfusion when presenting malaria, probably due to primaquine-induced hemolysis. Primaquine has been prescribed in Brazil for decades without prior assessment of G6PD status, posing a potential risk to the small proportion of G6PD-deficient individuals receiving this drug, demonstrated by series of hospitalized patients and fatal cases 42,47,48. A large population survey of G6PD deficiency in the Amazon region is ongoing and should provide valuable information that will help to guide safer policies.…”
Section: Plasmodium Vivax Epidemiologymentioning
confidence: 99%
“…Though oral chloroquine is usually safe, it has been demonstrated that pruritus can occur in around 20% of patients being treated for P. vivax infection,54 with risk of noncompletion of treatment. Adverse events associated with primaquine use, especially hemolysis, are of greater concern55 as they can lead to severe complications 48. An autopsy series of P. vivax patients found severe primaquine-induced hemolysis and associated complications as the main cause of death in two individuals 42.…”
Section: Malaria Control Interventionsmentioning
confidence: 99%